2008
DOI: 10.1007/s12094-008-0173-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of patients with early endometrial carcinoma: a systematic review

Abstract: A conservative approach in these patients can offer reasonable oncological security and the opportunity of fulfilling their maternal desires in selected cases. However, consideration should be taken regarding the potential adverse outcomes that have been recently published in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…All but one patient were disease free at the end of the study (one patient was undergoing the third round of progestin treatment for multirecurrent disease). The few other published studies on outcomes of repeat fertility-sparing treatment have reported similar findings,16,47,55,64,65,86 which suggests that progestin retreatment in the setting of initial complete response may be feasible and safe, albeit a temporary approach, for women who decline definitive treatment at the time of uterine-confined EC recurrence.…”
Section: Hormone Treatmentmentioning
confidence: 56%
See 3 more Smart Citations
“…All but one patient were disease free at the end of the study (one patient was undergoing the third round of progestin treatment for multirecurrent disease). The few other published studies on outcomes of repeat fertility-sparing treatment have reported similar findings,16,47,55,64,65,86 which suggests that progestin retreatment in the setting of initial complete response may be feasible and safe, albeit a temporary approach, for women who decline definitive treatment at the time of uterine-confined EC recurrence.…”
Section: Hormone Treatmentmentioning
confidence: 56%
“…The range of response rates published in the literature varies, with some studies reporting response rates between 42% and 62%48,54,60,68 and others reporting higher rates of 78%–100% 52,62,65,66,76,80. Factors that could account for these differences include 1) variations in treatment duration, as longer treatment durations could result in higher response rates,15,64 and 2) differences in definitions of “complete response”.…”
Section: Hormone Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of Mazzon and Shan a review by two pathologists specialising in gynaecology was carried out independently. In a previous review carried out by our group, we saw that according to the literature, there is a difference between inter and intraobserver of 40% [ 15 ], which is why a review by two pathologists is an established recommendation. In the study of two cases by Marton et al [ 14 ] there is no mention of hormonal receptors or of histological confirmation.…”
Section: Patient Selection For Conservative Surgical Treatmentmentioning
confidence: 99%